2018
DOI: 10.14814/phy2.13897
|View full text |Cite
|
Sign up to set email alerts
|

Ski drives an acute increase in MMP-9 gene expression and release in primary cardiac myofibroblasts

Abstract: Many etiologies of heart disease are characterized by expansion and remodeling of the cardiac extracellular matrix ( ECM or matrix) which results in cardiac fibrosis. Cardiac fibrosis is mediated in cardiac fibroblasts by TGF ‐ β 1 /R‐Smad2/3 signaling. Matrix component proteins are synthesized by activated resident cardiac fibroblasts known as myofibroblasts ( MFB ). These events are causal to heart failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
(144 reference statements)
0
15
0
Order By: Relevance
“…3 The key pathophysiological basis is the feedback cycle between HF and continuous differentiation of cardiac fibroblasts (CFs) into cardiac myofibroblasts, 4 which have a potent ability to divide and cause ECM overproduction. 5,6 This activation is mediated by the renin-angiotensin system and numerous neurohumoral factors, including angiotensin II (Ang II) and transforming growth factor β1 (TGF-β1). 3,5 Ang II promotes the release of catecholamine and aldosterone, up-regulates the expression of TGF-β1 in fibroblasts, and is a strong promoting factor for cardiac fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The key pathophysiological basis is the feedback cycle between HF and continuous differentiation of cardiac fibroblasts (CFs) into cardiac myofibroblasts, 4 which have a potent ability to divide and cause ECM overproduction. 5,6 This activation is mediated by the renin-angiotensin system and numerous neurohumoral factors, including angiotensin II (Ang II) and transforming growth factor β1 (TGF-β1). 3,5 Ang II promotes the release of catecholamine and aldosterone, up-regulates the expression of TGF-β1 in fibroblasts, and is a strong promoting factor for cardiac fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of cardiac fibrosis includes disruption of normal myocardial construction and abnormal extracellular matrix (ECM) accumulation 3 . The key pathophysiological basis is the feedback cycle between HF and continuous differentiation of cardiac fibroblasts (CFs) into cardiac myofibroblasts, 4 which have a potent ability to divide and cause ECM overproduction 5,6 . This activation is mediated by the renin–angiotensin system and numerous neurohumoral factors, including angiotensin II (Ang II) and transforming growth factor β1 (TGF‐β1) 3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SKI is dysregulated and sequestered to the cytoplasm in a post-MI model of cardiac remodeling, suggesting that it contributes to fibroblast phenotype regulation [12]. We found that SKI also modulates MMP-9 expression and releases from primary cardiac fibroblasts, indicating that it may also influence the deposition and removal of ECM during post-MI wound healing [31]. As SKI's effects in cardiac fibroblasts are substantial and robust, it is possible that its functions within the cell extend beyond SMAD inhibition.…”
Section: Introductionmentioning
confidence: 66%
“…6 (continued) expression of αSMA and ED-An FN [11,12] in primary cardiac myofibroblasts. It was also established that SKI overexpression in primary cardiac myofibroblasts upregulates MMP-9 transcription and secretion [31], and its chronic expression represses autophagy-mediated survival responses which normally enable the pro-fibrotic phenotype to persist [60]. Recently it was found that SKI functions to inhibit pro-fibrotic signaling in cardiac myofibroblasts via SMADindependent MAPK signaling [61], suggesting that its functions are far more pleiotropic than initially described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation